Octamer-primed cycle sequencing using dye-terminator chemistry. - Jones, L B (1998)
Octamer Sequencing Technology, OST, is a method of DNA sequencing using single octamer oligonucleotides to prime cycle sequencing reactions. This sequencing strategy is faster than a traditional primer-walking strategy, since access to this optimized octamer library eliminates delays associated with designing and synthesizing gene specific primers. In this report, OST has been optimized for fluorescent, dye-terminator cycle sequencing reactions to facilitate parallel processing of samples. The successful adaptation of OST to an automated sequencing platform and the design of and access to an octamer library are critical steps towards developing an efficient 'closed-loop' DNA sequencing system.